Cyclohexyl Ketone Inhibitors of Pin1 Dock in a Trans-Diaxial Cyclohexane Conformation - Xu, Guoyan G.; Slebodnick, Carla; Etzkorn, Felicia A. (PLOS ONE, 2012)
Cyclohexyl ketone substrate analogue inhibitors (Ac–pSer-Ψ[C = OCH]-Pip–tryptamine) of Pin1, the cell cycle regulatory peptidyl-prolyl isomerase (PPIase), were designed and synthesized as potential electrophilic acceptors for the Pin1 active site Cys113 nucleophile to test a proposed nucleophilic addition-isomerization mechanism. Because they were weak inhibitors, models of all three stereoisomers were docked into the active site of Pin1. Each isomer consistently minimized to a trans-diaxial cyclohexane conformation. From this, we hypothesize that Pin1 stretches substrates into a trans-pyrrolidine conformation to lower the barrier to isomerization. Our reduced amide inhibitor of Pin1 adopted a similar trans-pyrrolidine conformation in the crystal structure. The molecular model of 1, which mimics the l-Ser-l-Pro stereochemistry, in the Pin1 active site showed a distance of 4.4 Å, and an angle of 31° between Cys113-S and the ketone carbon. The computational models suggest that the mechanism of Pin1 PPIase is not likely to proceed through nucleophilic addition.